2006
DOI: 10.1007/s00404-006-0223-2
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, folic acid and B12 serum levels in pregnancy complicated with preeclampsia

Abstract: It is concluded that in our study homocysteine levels are significantly elevated in patients with preeclampsia compared with control group, while no vitamin deficiencies were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 18 publications
8
51
4
1
Order By: Relevance
“…7 Several other studies were in consonance with the present study. 5,6,[8][9][10] On the contrary Zeeman GG et al did not agree with our observations and there was no significant difference in maternal serum levels of homocysteine between pre-eclampsia and normal pregnancy (5.1±1.7 μmol/l vs 4.7±1.3 μmol/l p value =0.56) and they stated that serum homocysteine levels were not helpful in the prediction of PE. 11 Hietala R et al also stated that there was no difference between pre-eclampsia and normotensive women (6.42, 7.55μmol/l vs 6.45, 7.34 μmol/l).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…7 Several other studies were in consonance with the present study. 5,6,[8][9][10] On the contrary Zeeman GG et al did not agree with our observations and there was no significant difference in maternal serum levels of homocysteine between pre-eclampsia and normal pregnancy (5.1±1.7 μmol/l vs 4.7±1.3 μmol/l p value =0.56) and they stated that serum homocysteine levels were not helpful in the prediction of PE. 11 Hietala R et al also stated that there was no difference between pre-eclampsia and normotensive women (6.42, 7.55μmol/l vs 6.45, 7.34 μmol/l).…”
Section: Discussioncontrasting
confidence: 96%
“…Premlata et al showed the mean levels of severe PE and mild PE 15.9±6.3 vs 12.3±4.2 (p value =0.01). 4 Several other studies were in consonance with the her results such as Khosrowbeygi A et al and Makedos G et al 6,10 Based on the findings of present study it can be concluded that maternal serum homocysteine seems to have a causal role in pathogenesis of pre-eclampsia, however measurement of homocysteine concentration did not determine the severity of pre-eclampsia. In present study the pre-eclamptic group had higher incidence of caesarean sections (56.66%).…”
Section: Discussionsupporting
confidence: 89%
“…There was no between-group difference in the folic acid and vitamin B12 levels. The group of women with preeclampsia was associated with a higher rate of cesarean section, IUGR (50%) and abruptio placentae (20).…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed the mean homocysteine level (6.758±2.062 μmol/L) and median (6.400 μmol/L) calculated for women with preeclampsia to exceed the respective values recorded in the control group of women free from preeclampsia (6.014±1.539 μmol/L and 5.800 μmol/L); however, the between-group difference in homocysteine levels did not reach statistical significance. Makedos et al (20) compared homocysteine levels in a group of pregnant women with preeclampsia and control group free from preeclampsia and found the mean homocysteine level to be significantly increased in the former (11.11 μmol/L vs. 6.40 μmol/L, p<0.001). There was no between-group difference in the folic acid and vitamin B12 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease), hypothyroidism, birth defects and late pregnancy complications, such as preeclampsia, intrauterine grow retardation, preterm birth and intrauterine fetal death and abruption of placenta [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%